UDP-Glycosyltransferase Genes in the Striped Rice Stem Borer, Chilo suppressalis (Walker), and Their Contribution to Chlorantraniliprole Resistance - Zhao, Jun (Int J Mol Sci, 2019)
Uridine diphosphate glycosyltransferases (UGTs) are multifunctional detoxification enzymes, which are involved in metabolizing various chemicals and contribute to the development of insecticide resistance. However, the possible roles of UGTs in chlorantraniliprole resistance in Chilo suppressalis have rarely been studied in detail. Based on genome data, 24 UGT genes in C. suppressalis belonging to 11 families were identified, which were designated by the UGT nomenclature committee. Synergism assay data suggested that UGTs are potentially involved in chlorantraniliprole resistance in C. suppressalis. CsUGT40AL1 and CsUGT33AG3 were significantly overexpressed in the chlorantraniliprole resistant strain (12.36- and 5.34-fold, respectively). The two UGTs were highly expressed in the larval Malpighian tubules, fat body, and midgut; however, expression was lowest in the head. Injection of individual dsRNAs reduced the expression of the two target genes (by 69.34% and 48.74%, respectively) and caused significant higher larval mortality (81.33% and 54.67%, respectively). Overexpression of CsUGT40AL1 and CsUGT33AG3 was potentially involved in chlorantraniliprole resistance in C. suppressalis, as confirmed by the RNAi assay. Our findings suggest that overexpression of UGTs may contribute to chlorantraniliprole resistance in C. suppressalis.